Sistem Pendukung Keputusan Berbasis Web Untuk Penentuan Ruang Terbuka Hijau Di Kota Makassar Menggunakan Metode PSI - Rhafly Dwi Saputra Tamal; Joko Dwi Santoso (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Green Open Space (RTH) according to Law No. 26 of 2007 concerning Spatial Planning is an elongated area/lane and/or clustered, whose use is more open, where plants grow, both those that grow naturally or those that are intentionally planted. The Preference Selection Index (PSI) method is a method used to solve multi-criteria decision-making (MCDM). In the proposed method that it is not necessary to establish the relative importance of the attributes. There is no need for attribute weighting computations involved in the decision-making in this method. This method is useful when there is a conflict in determining the relative importance of attributes. The result of this study is to build an application that can help the Makassar Spatial Planning Office in managing the environment of green open spaces for the benefit of the general public, every year the Spatial Planning Office conducts a review of the amount of public interest in every open green open space (RTH). The determination of the high value of interest is based on the benchmarks that have been set as eligibility standards, That the alternative to get the highest rating is Karebosi Field 1 with a total score of 1, while the lowest rating is Hasunuddin Field 1 with a total score of 0.75..